ASEAN Community and Prospects for the Development of UIN Raden Fatah Palembang - Aflatun Mukhtar; Aristophan Firdaus (Jurnal Studi Sosial dan Politik, 2020)
By entering the era of higher education industrialization, Indonesia is required to improve itself so that it can compete with other ASEAN countries. According to several university ranking data, the quality of Indonesian education is still below Singapore and Malaysia. The portrait of the quality of Indonesian higher education is still very vulnerable to injustice and lack of equity Competition for a professional workforce, having mature skills and being equipped with good language skills are prerequisites for competing fairly with other ASEAN member countries. Of course, Raden Fatah State Islamic University Palembang, which has approximately 25,000 students consisting of 39 study programs and 500 lecturers, both domestic and foreign graduates, has great potential to be involved in preparing a reliable workforce in their fields. The quality of the workforce must be supported by the quality of education held in each country, including UIN Raden Fatah Palembang. With good quality, the country's human resources are ready to compete in the ASEAN labor market. The factors that determine the effort to improve the quality of UIN Raden Fatah Palembang in facing the ASEAN Community include: vision and mission; rules; governance guidelines; student body; human Resources; infrastructure; Tri Dharma College; international cooperation; visiting lecturer; and Asean issues. All of these factors are the basis for higher education management.